FAMILY HISTORY, KNOWLEDGE, AND RESTING PATTERNS ASSOCIATED WITH HYPERTENSION: CASE-CONTROL STUDY: Riwayat Keluarga, Pengetahuan, dan Pola Istirahat terkait dengan Hipertensi (Studi Case-Control) - Rizqiyah Syafitri, Nadia; Qurniyawati, Eny; Nityasani, Renaningtyas; Ssekalembe, Geofrey (Universitas Airlangga, 2025)
Background: Non-communicable diseases are the leading cause of death worldwide, responsible for approximately 75% of global mortality. Hypertension, a significant contributor to NCD-related deaths, affects an estimated 1.28 billion adults globally and is often referred to as